Pak Rama’s Education as a Prevention of Dehydration and Non-Communicable Diseases among Workers in Hot Working Environments - Mayasari, Diana; Saftarina, Fitria; Isti Anggraini, Dian; Carolia, Novita (Community Development Journal, 2024)
Working in a hot environment can disrupt the balance of body temperature so that the body tries hardly to control the heat which can cause a lack of fluids and is called dehydration. Dehydration can affect cognitive performance, causing decreased productivity and increased risk of work accidents, and in the long term can trigger some non-communicable diseases such as hypertension, urinary tract disease, obesity and others. Pak Rama Education (Active Workers Diligently Drink Water) is an educational and empowerment activity for the worker community, especially those who work in hot environments, in an effort to prevent dehydration and non-communicable diseases. The aim of this activity was to increase workers' knowledge about healthy hydration and increase workers' ability to assess hydration status independently. This activity was carried out using the education method about healthy hydration and a demonstration of how to assess hydration status using a urine color chart. Pak Rama's activity was held on 17th November 2022 at PTPN VII Unit Way Berulu South Lampung. The participants were 50 workers consisting of management officers, factory and plantation workers. From the evaluation results, it was found that the average pre-test score of participants was 66.7 and there was an increase of participants' knowledge about healthy hydration which was seen from the increase in the average score on the post-test, namely 86.6. Based on analysis using the Wilcoxon test, it was found that there was a statistically significant difference between average pretest and posttest scores. The results of the assessment of participants' ability to assess hydration status using a urine color chart were also found increase. Pak Rama's education has proven effective in increasing workers' knowledge about healthy hydration and their ability to assess hydration status independently. Keywords: Healthy hydration; worker’s health; Pak Rama education; non-communicable diseases; urine color chart